Prevalence of chronic non-specific low back pain among caregivers of stroke survivors in Kano, Nigeria and factors associated with it: A cross-sectional study - Abdullahi, Auwal; Aliyu, Kamilu; Hassan, Auwal Bello; Sokunbi, Ganiyu Oluwaleke; Bello, Bashir; Saeys, Wim; Truijen, Steven (Frontiers in Neurology, 2022)
Purpose: Low back pain (LBP) may have a specific or non-specific cause such as abnormal posture or repetitive tasks. For instance, lifting and transferring patients during caregiving for stroke survivors may predispose the caregivers to LBP. Objectives: The aim of this study is to determine the prevalence of chronic non-specific LBP and factors associated with it in caregivers of stroke survivors. Method: The research design used is cross-sectional study design. Participants of the study were caregivers of stroke survivors who were at least 18 years old. They were included if they had at least one month experience with caregiving for at least one hour per day. Presence of LBP and level of disability were assessed using participants’ self-report and Rolland Morris Low Back Pain Disability Questionnaire respectively. The data collected was analyzed using descriptive, Chi-square statistics and Binary Logistics Regression. Result: Three hundred caregivers in which 207 and 93 were males and females respectively, participated in the study. The results showed that, there was a high prevalence (64.3%) of LBP among the caregivers. The prevalence is significantly associated with gender (X2=24.805, p<0.001), age (X2=14.02, p=0.029), occupation (X2=58.919, p<0.001) and duration of caregiving (X2=26.627, p<0.001) of the study participants. Similarly, level of disability due to the presence of LBP among the study participants is significantly associated with gender (X2=26.308, p<0.001), occupation (X2=43.810, p<0.001), duration of caregiving (X2=7.416, p=0.025), and the nature of the caregiving (X2=13.754, p<0.001).